WTO and Agricultural Trade – Some Issues and Perspectives (KASBIT Business Journal, 2008)
In the Uruguay Round Agreement, the rules governing agricultural trade were changed fundamentally.Members have agreed to convert all non-tariff agricultural barriers (NTBs) to ordinary tariffs, tobind all agricultural tariffs, and to subject them to reductions. Members have also agreed toestablish tariff-rate quotas (TRQs) to preserve historical trade levels and to create some new tradeopportunities in highly protected markets. Some reductions in agricultural tariffs also were achieved.Nonetheless, agricultural tariffs remain to be very high for some politically sensitive products insome developing countries, limiting the trade benefits from the new rules. The failure of tradenegotiators, who met at Geneva to narrow their differences on the modalities of compiling detailedcuts in tariffs and agricultural subsidies, is no doubt a setback to multilateral trade negotiations.This paper analyses the impact of WTO agricultural trade policies on developing economies. Anattempt is made to discuss the benefits and risks for agricultural trade associated with the changesin international trade. The paper also delves agricultural reforms that were introduced by the GATTprior to 1995. The paper examines whether the reforms were useful for the developing countriesor not. By way of a summing up, some insights are set out to provoke analysis and debate on thecontroversial WTO talks.
Keywords: WTO; Agriculture Tariff; GATT; Market Access; Developing Countries; Quotas